Factors Influencing Intention to Use Electronic Payment Systems: The Case of Students in Famagusta - Boraei, Mohanned (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
There has been a tremendous growth in internet and information and communication technology (ICT) throughout the last 2 decades, in addition to the revolutionary evolution in the electronic payment systems (EPS) that changed the e-commerce world totally and enabled to make enormous business transactions within few minutes. Therefore this study try to establish and clarify whether; (1) knowledge about e-commerce has direct effect on students intentions to use EPS, (2) perceived reputation towards EPS has direct effect on students intentions to use EPS, (3) general satisfaction from e-commerce has direct effect on students intentions to use EPS, (4) specific satisfaction from EPS has direct effect on students intentions to use EPS. In this study a comprehensive literature review was engaged in order to initially conceptualize the relationship between all of factors mentioned earlier and their possible effect on customer intentions to use EPS, the literature review goes from the base of the Pyramid to its top (goes from wide to narrow). A sample consist of 310 respondents was chosen to examine the proposed hypotheses using regression analysis, the findings highly supported the claimed hypotheses that all the factors mentioned earlier influence and have positive relationship with the customer’s intentions to use EPS. Keywords: Buying behavior, intention to use EPS, e-commerce knowledge, General satisfaction, specific satisfaction, and perceived reputation

ÖZ : İnternet ve BİT alanında son yirmi yılda yaşanan devasa gelişmelerin yanı sıra, elektronik ödeme sistemlerinin (EÖS) devrim niteliğindeki evrimi de günümüzün eticaret dünyasını tümüyle değiştirerek dakikalar içerisinde oldukça büyük ticari işlemler gerçekleştirilmesine olanak sağlamıştır. Buna bağlı olarak, söz konusu çalışmanın amacı müteakip ifadelerin doğruluğunu araştırmak ve açıklığa kavuşturmaktır; (1) e-ticaret hakkında bilgi sahibi olmanın müşterilerin EÖS kullanımına olan yönelimleri üzerinde etkisi vardır, (2) EÖS’nin algılanan itibarının müşterilerin EÖS kullanımına olan yönelimleri üzerinde etkisi vardır, (3) e-ticaret konusundaki genel memnuniyetin müşterilerin EÖS kullanımına olan yönelimleri üzerinde etkisi vardır, (4) EÖS’ye olan spesifik memnuniyetin müşterilerin EÖS kullanımına olan yönelimleri üzerinde etkisi vardır. Bu çalışma kapsamında öncelikle bashi geçen tüm faktörler arasındaki ilişkinin vemüşterilerin EÖS kullanımlarına olan etkilerinin kavramsallaştırılması amacıylagerçekleştirilen kapsamlı literatür taraması Piramidin tabanından üst noktasına doğruilerlemektedir (geniş alandan dar alana doğru ilerlemektedir). Öne sürülen hipotezlerin bağlanım analizi kullanılarak değerlendirilmesi amacıyla söz konusu model kapsamında toplam 310 denek seçilmiştir. Sonuçlar, bahsi geçen faktörlerin müşterilerin EÖS kullanımını etkilediğini ve EÖS kullanımlarına dair yönelimleri ile olumlu bir ilişkiye sahip olduğunu öne süren hipotezleri ziyadesiyle desteklemektedir. Anahtar Kelimeler: Satın alma davranışı, EÖS kullanma yönelimi, e-ticaret bilgisi, genel memnuniyet, spesifik memnuniyet, ve algılanan itibar
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2016. Supervisor: Assist. Prof. Dr. Emrah Öney.
Keywords: Marketing Management; Electronic commerce--Mobile commerce; Buying behavior; intention to use EPS; e-commerce knowledge; General satisfaction; specific satisfaction; perceived reputation; Business Administration